Power factor improvement on LED lamp driver using BIFRED converter - Moh. Zaenal Efendi; Farid Dwi Murdianto; Fito Ardli Fitri; Luluk Badriyah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents the implementation of a power converter to improve power factor for LED lamp driver. The power converter which used in this system is the integration of boost and flyback converter (boost integrated flyback rectifier energy storage DC-DC/BIFRED). The boost converter as power factor correction (PFC) works on discontinuous conduction mode (DCM) operation to make the resistive converter. Thus, when a rectifier circuit supplies a resistive load, the load current that flows back to the source will have the same waveform as the voltage and it makes the power factor value next to 1 (unity). According to experiment results, the BIFRED converter as LED lamp driver can improve power factor from 0.84 to become 0.98 and this driver circuit also meets the line-current harmonic limits set by IEC61000-3-2 class C.